A Literature Review On Islamic Estate Planning From Year 2014 To 2019 - Muhammad Muiʻzz Abdullah; Naimah Mohamad Nasir; Nasrul Hisyam Nor Muhamad; Abdul Bari Awang; Mek Wok Mahmud; Muhammad Ridhwan Ab. Aziz (University of Nebraska-Lincoln, Lincoln, 2024)
Indexed by SCOPUS/ERA